0690 Enlarged Basal Ganglia Perivascular Spaces And Sleep Parameters. A Population-based Study. (12th April 2019) - Wasey, Waiz A; Del Brutto, Oscar H; Mera, Robertino; Brutto, Victor Del; Castillo, Pablo R
Abstract: Introduction: Perivascular spaces (PVS) are involved in mechanisms of brain interstitial fluid and metabolic waste clearance. Since most of this clearance occurs during sleep, it is plausible that sleep-related disorders favor PVS dilatation. Knowledge on the association between enlarged basal ganglia (BG) PVS and sleep disorders is limited. Here, we aimed to assess the association between sleep parameters and enlarged BG-PVS in older adults. Methods: Community dwellers aged ≥60 years were interviewed with the Pittsburgh sleep quality index and underwent MRI for identification of enlarged BG-PVS and other neuroimaging signatures of cerebral small vessel disease. Then, a representative random sample of the study population underwent a single-night polysomnography (PSG). Using logistic regression models, we evaluated whether sleep quality, sleep efficiency and the apnea-hypopnea index (AHI) associate with enlarged BG-PVS, after adjusting for demographics, cardiovascular risk factors, neuroimaging signatures of cerebral small vessel disease and other relevant confounders. Results: The association between sleep quality and enlarged BG-PVS, assessed in 338 individuals, was significant in the univariate model, but the significance was taken away by the effect of confounders. The association between PSG parameters and enlarged BG-PVS was assessed in a random sample of 97 individuals. Logistic regression models showed a significant association between poor sleep efficiency and enlarged BG-PVS ( p =0.045). In contrast, there was no association between the AHI and BG-PVS. Conclusion: Poor sleep efficiency is independently associated with enlarged BG-PVS, suggesting that sleep may influence structural changes in these fluid-filled cavities. Support (If Any): Study supported by Universidad Espíritu Santo - Ecuador, Guayaquil - Ecuador.